A process model for organizational action research - Henriques, T. A.; O'Neill, Henrique (European Academy of Management Conference, EURAM 2018, 2018)
Organizational Action Research has already proven to be a strong approach to promote Organization Development while generating Actionable Knowledge. Being a solid approach with evident results, there is still room for its renewed application within companies, through the collaboration between academics and practitioners, in order to potentiate new knowledge while promoting the development of organizations as working communities. In this sense, steps can be taken to disseminate Action Research inside the core of organizations, to divulgate its high-potential and providing simple and clear views of the process. This article intends to contribute to this dimension: highlighting its main sub-processes, related data, and relationships between the action and the research cornerstones. It provides a simplified overview of a pragmatic process meta-model for Action Research, which has been tested and applied with success using a Design Science Research approach. It has been developed with a clear intent of simplification, in order to attract new organizational researchers, stimulating their participation in collaborative research initiatives which can promote the development of their own organizations.